Renal vascular morphology and their significance in predicting accessories - M, Venkataramulu; N, Vinaykumar; LC, Prasanna (International Journal of Research in Medical Sciences, 2017)
Background:Renal arteries presented great morphological variations in their emergence, frequency, and ramification pattern. Therefore, this study was aimed to establish the possible relationship between the caliber of the renal artery and existence of the accessory renal arteries. Methods:Fifty kidneys obtained from fresh cadavers were subjected for corrosion cast to determine the diameter of main and accessory renal arteries. Results:In our study, we found that the incidence of single accessory renal artery (24%) was higher than the presence of two or more accessory arteries (4%) from the aorta.However, no significant difference was observed in the number of accessory renal arteries with respect to right and left side.Superior polar type of accessory renal artery was seen only on the left side in 2% of the specimens, and inferior polar arteries were found in 6% of the specimens on both the sides. The hilar type of accessory renal arteries were found in 8% and 6% of the cases on right and left sides respectively. Conclusion:The diameter of the main/principle renal artery in kidney presenting the accessory renal arteries was significantly less than that of the kidney with single renal artery.